The mechanical properties and structural performance of hybrid fibre reinforced concrete composite - Othman, Faezah Asmahani (2014)
Fibres in concrete provide a mean of preventing crack growth. Short discontinuous fibres have the advantage of being uniformly mixed and dispersed throughout the concrete. In this research, the mechanical properties of hybrid fibre reinforced concrete composite (HyFRCC) were investigated by combining polypropylene fibre (PP) with steel fibre (ST). PP fibre is good in preventing micro cracks while steel fibre is reliable in preventing macro cracks in concrete. Specimens incorporated with ST and PP fibres were in the mix proportion of 100-0%, 75-25%, 50-50%, 25-75%, and 0-100% at volume fraction of 0.5%, 1.0%, and 1.5%. Compression test, flexural test, splitting tensile test, flexural toughness, and Young’s Modulus were carried out to determine the mechanical properties of HyFRCC. By combining these two fibres in concrete, the crack growth reduced where PP fibre was found to improve the tensile strain capacity, while ST fibre contributed to the improvement on the ultimate tensile strength. HyFRCC specimens also delayed the failure phenomena due to the different tensile strength of PP and ST fibres compared with the sudden failure experienced by plain concrete. The experimental test results found that HyFRCC with the combined mix proportion of 75% ST fibre + 25% PP fibre at volume fraction of 1.5% can be adjudged as the optimum percentage. This optimum percentage was then applied in reinforced concrete beams to study the structural performance in flexural of shear. In conclusion, HyFRCC beam is tougher and stronger compared with the control beam based on the load-deflection relationship. Crack pattern of HyFRCC beam shows that the crack width and crack spacing reduces compared with the control beam. The effect of combining ST and PP fibres in concrete enhances the tensile strength, the concrete strain hardening and flexural toughness.